Preparation, Characterization and Release Studies of Naproxen-loaded Microspheres from Natural Gums (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Use of biodegradable natural materials as pharmaceutical excipients is increasing. In this study, Naproxen loaded microbeads were produced, using natural gums obtained from Cedrela odorata and Irvingia gabonensisObjective: Aim is to evaluate physicochemical properties of the gums and determining release properties of the formulations.Materials and Methods: Cedrela gum (CG) and Irvingia gum (IG) were extracted from Cedrela odorata and Irvingia gabonensis respectively, and characterized by viscosity, density and pH measurements. Naproxen microbeads were formulated (Formulation A2 to A9) with the gums and sodium alginate using ionotropic gelation method. Cross linkers (CaCl2 or Al2[SO4]3) were used at different curing times. Scanning electron microscopy (SEM), photomicrographs, entrapment efficiency and release profiles of the formulations were determined.Results: Physicochemical property tests showed that the gums possess good flow, viscosity and they presented with acidic pH. There was no interaction between FT-IR spectra of the gums and naproxen. SEM revealed microbeads to be almost spherical, having slightly rough surfaces. Microbeads from Formulation A6 had the largest particle size (1500±163.2 µm) while Formulation A9 possessed the smallest particle size A9 (491.6±191.7 µm). All the formulations gave high entrapment efficiency (80 – 96%); microbeads containing IG (Batch A6 – A9) had higher values than those formulated with CG gum (Batch A2 – A5) (p > 0.05). Batch A6 (containing IG with CaCl2 at curing time of 15 minutes) gave the highest drug release (p < 0.05).Conclusion: Gums obtained from Cedrela odorata and Irvingia gabonensis possessed good physicochemical properties and produced microbeads suitable for the controlled release of Naproxen. Formulations containing Irvingia gum showed higher drug release and better entrapment